Rho GTPase regulatory proteins contribute to podocyte morphology and function - Foxman, Emily; Ibrahim, Sajida; Takano, Tomoko (McGill Science Undergraduate Research Journal, 2023)
Podocytes are a critical cellular component of the glomerular filtration barrier, whose strict permselectivity prohibits the passage of large proteins and charged species into the urine. Phenotypic variability or injury of these highly specialized cells can lead to proteinuria and has been linked with altered activity of Rho GTPases, which are strongly associated with the actin cytoskeleton. Notable regulators of these intracellular molecular switches are called guanine nucleotide exchange factors (GEFs), GTPase-activating proteins (GAPs), and guanine nucleotide dissociation inhibitors (GDIs). In this study, the roles of several GEFs in podocyte morphology and activity were investigated, including ECT2, ARHGEF2, ARHGEF26, and ARHGEF40. Results from RhoA and Rac1 G-LISA Activation Assays indicated that the absence of ARHGEF40 impairs epidermal growth factor (EGF)-stimulated RhoA and Rac1 activation, whereas knockout of ARHGEF2 and ARHGEF26 may selectively diminish RhoA activation. Furthermore, filopodia formation was hindered for the ARHGEF40 knockout. There are a number of additional investigations underway to understand Rho GTPase regulatory proteins, including the elimination of new sets of GEFs and GAPs in vivo. It is hopeful that these studies can provide insights into potential novel therapeutic strategies for proteinuria.